2004
DOI: 10.1081/erc-200027354
|View full text |Cite
|
Sign up to set email alerts
|

Is Serum Ferritin High in Patients with Diabetic Retinopathy? A Controlled Study

Abstract: It is suggested that an excessive absorption and storage of dietary iron might contribute in the pathogenesis of type II diabetes mellitus and its complications. However, previous studies had methodological problems including design, lack of matched controls and unspecified inclusion criteria. The aim of the study was to evaluate the relationship between diabetic retinopathy and serum ferritin levels in well-defined diabetic patients and controls. The study population comprised of 3 groups: patients with type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Moreover, the authors reported that there was no apparent correlation between serum iron or serum ferritin and HbA1c concentration between the groups comprised of individuals with T2DM. Thus, the authors concluded that iron does not appear to have a major role in the development of T2DM or diabetic retinopathy (385). Given the overall small sample size (n = 91), which was stratified into groups of 3, it appears that one cannot draw any valid conclusions based upon these data.…”
Section: Iron and T2dmmentioning
confidence: 71%
“…Moreover, the authors reported that there was no apparent correlation between serum iron or serum ferritin and HbA1c concentration between the groups comprised of individuals with T2DM. Thus, the authors concluded that iron does not appear to have a major role in the development of T2DM or diabetic retinopathy (385). Given the overall small sample size (n = 91), which was stratified into groups of 3, it appears that one cannot draw any valid conclusions based upon these data.…”
Section: Iron and T2dmmentioning
confidence: 71%